Maternal near miss: Unraveling our experience in the tertiary care hospital of Andaman and Nicobar Islands - Charu Sharma; Anita Yadav; Manju Mehrotra; Mrinmoy Kumar Saha; Rupali R Tambe (Wolters Kluwer Medknow Publications, 2021)
Context: Women who survive life-threatening complications related to pregnancy and delivery have many common aspects with those who die of such complications. This similarity brought forward the near miss concept in maternal health. Analysis of the similarities, differences, and the relationship between these two groups of women provide a complete assessment of quality of maternal health care. Aims: The aim of this study is to assess the baseline indices of maternal near miss (MNM) and analyze the quality of care at a tertiary care center in Andaman and Nicobar Islands. Settings and Design: Facility-based, cross-sectional study. Subjects and Methods: The study was conducted for a period of 18 months from January 1, 2015, to August 31, 2016. Cases, who met the World Health Organization (WHO) criteria of severe obstetric morbidity, were included and followed up during their hospital stay and till their discharge or death. Quality of maternal health care was assessed through the WHO near-miss criteria and criterion-based clinical audit methodology. Statistical Analysis Used: Descriptive statistics using mean and percentages and Student's t-test were used. Results: Among 4720 women who delivered in our hospital, there were 4677 live births, 52 patients were near miss, and there were 9 maternal deaths. The MNM incidence ratio was 11.11%, the MNM mortality ratio was 5.77, and the mortality index 14.75%. The most common cause of maternal morbidity was hemorrhage followed by hypertensive disorders. Conclusions: Improving referral systems, effective use of critical care, and evidence-based interventions can potentially reduce severe maternal outcomes.